Supporting and Studying Organizational Change for Introducing Welfare Technologies as a Sociomaterial Process - Bruzzone, Silvia; Crevani, Lucia (Frontiers in Psychology, 2022)
Welfare technologies for older people is a rapidly expanding sector providing a way to tackle the challenge of an aging population. Despite their promise in terms of advances in care services and in financial savings, their use is still limited. Their design and implementation remain problematic as they require changes in the working practices through the coordination of a multiplicity of actors. In order to address these challenges, the need for change is often expressed in terms of lack of working methods adapted to the scope. This has led to the proliferation of different toolkits, guidelines, models, etc.. Such methods, however, have often a linear understanding of an implementation project and thus fail to take into consideration the emergent and situated character of processes leading to the adoption of welfare. This article aims at proposing an alternative way of providing support for introducing these technologies by initiating a process for organizational change. Change is understood as produced by practitioners – in collaborations with researchers - and not brought by researchers to practitioners. To this end, inspired by the tradition of intervention-research, a learning process at the cross-road of different practices and objects was initiated. At the center of attention is the sociomaterial process in which different communities of practitioners interact upon the co-creation of a checklist, as new working method. The focus of attention is not the artifact in itself but how it emerges through successive interactions and iterations between different objects, practitioners and researchers resulting in a joint sociomaterial process reconfiguring power relations and the object of work connected to welfare technologies. In other words, developing a new working method artefact takes place in a process in which practitioners, researchers and contextual objects interact and become with one another.